MODEL PEMBERDAYAAN PASAR TRADISIONAL BERBASIS EKONOMI KERAKYATAN DI KOTA SEMARANG - Wijayati, Putri Agus (Paramita: Historical Studies Journal, 2013)
This study aims to discover the empowerment model of traditional market as a place for small-scale entrepreneurs in the city of Semarang. In the first year of using historical research has produced a historical description that the traditional market in the colonial era was able to demonstrate its existence as a place of trade for market participants and was able to compete with the private market. The empowerment model is packaged in the form of labor market discipline, regularity in the market area, the space flexibility for the market visitor and availability of parking spaces for the towing animals. The description of traditional market currently dominated by slums, congested, muddy, narrow access for buyers and vendors stalls are disorganized was derived from field research. If the historical description is combined with the today market description, it will produce a prototype of an effective and strong traditional market so that traditional traders in the city of Semarang have empowerment. Stakeholder participantsÃ¢â‚¬â„¢ model is used as alternative models to empower all the traditional market potential. Keyword:Ã‚Â  empowerment,Ã‚Â  economic community-based, traditional marketÃ‚Â Penelitian ini bertujuan untuk menemukan model pemberdayaan pasar tradisional sebagai tempat wirausaha skala kecil di Kota Semarang. Pada tahun pertama menggunakan historical research telah menghasilkan deskripsi historis bahwa pasar tradisional era kolonial mampu menunjukkan eksistensinya sebagai tempat perdagangan pelaku pasar dan mampu bersaing dengan pasar swasta. Model pemberdayaan dikemas dalam bentuk disiplin pegawai pasar, ketertiban di dalam lahan pasar, keleluasaan jalan bagi pengunjung pasar, dan ketersediaan lahan Ã¢â‚¬ÂparkirÃ¢â‚¬Â bagi hewan penarik. Melalui field research, diperoleh deskripsi pasar tradisional saat ini lebih didominasi kumuh, sesak, becek, akses pembeli sempit, dan lapak PKL tidak beraturan. Deskripsi historis dipadukan dengan deskripsi pasar dewasa ini dihasilkan prototype pasar tradisional yang efektif dan kuat agar pedagang pasar tradisional di Kota Semarang memiliki keberdayaan. Model partisipan stakeholder dijadikan alternatif guna memberdayakan semua potensi pasar tradisional. Keyword:Ã‚Â  pemberdayaan, ekonomi kerakyatan, pasar tradisional. Ã‚Â  Ã‚Â